Thin film material with narrow hysteresis width as well as preparation method and application of thin film material
By doping gadolinium and titanium into the vanadium dioxide film to regulate its phase change characteristics, the problem of slow sensor response speed, poor stability and hysteresis width results in measurement deviation, and the film material with narrow hysteresis width is realized, which improves the performance and application range of the sensor.
Patent Information
- Application Number
- CN202411859498.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-17
AI Technical Summary
Existing temperature sensors have problems such as slow response speed, poor long-term stability and hysteresis width leading to measurement deviations, which limit their effective application in key areas such as environmental monitoring.
By doping the vanadium dioxide film, gadolinium and titanium are introduced, and as impurity ions, it effectively replaces or destroys the V4+-V4+ covalent bond of the vanadium ions, regulates the phase change characteristics of the film, and prepares a film material with a narrow hysteresis width.
The film material with a narrow hysteresis width is achieved, which improves the sensor's response speed and long-term stability, and can more accurately reflect temperature changes, and is suitable for environmental monitoring and other key areas.
Smart Images

Figure CN119592913A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sensor technology, and mainly to a narrow hysteresis width thin film material and a preparation method and application thereof. Background Art
[0002] As science and technology develop rapidly, sensor technology plays an important role in many fields, and its application in the field of environmental monitoring is even more critical. As the core component of the environmental monitoring system, temperature sensors accurately measure and quickly respond to temperature changes, which are key elements for effective monitoring. In environmental monitoring scenarios such as temperature detection in urban ambient air quality monitoring stations and industrial production heat emission monitoring, the performance requirements of temperature sensors are extremely stringent. However, existing temperature sensors have many defects, and their response speed is obviously insufficient. In early warning scenarios such as forest fires, sensors need to be able to respond to rapid changes in temperature in an instant and provide accurate temperature data in a timely manner so as to take effective fire prevention and fire extinguishing measures. However, due to the limitations of materials and structures, the signal response of existing sensors often has a delay, and they cannot quickly capture rapid temperature fluctuations, which leads to misjudgment of disaster situations or delays in the best response time. Its long-term stability also needs to be solved urgently. The performance of sensors will be affected by erosion and interference when exposed to complex and harsh environments for a long time, which can easily lead to increased measurement errors or even failure, which not only increases the high replacement cost, but also threatens the reliability and effectiveness of monitoring work.
[0003] Vanadium dioxide (VO2) undergoes high-speed reversible phase transition under the influence of external factors such as thermal field, laser, electric field, etc. due to its unique metal-semiconductor phase transition performance. Before the phase transition, it presents a high resistance value, similar to typical semiconductor materials. When the temperature exceeds 68°C or is stimulated by other external stimuli to cause the phase transition, the resistance of VO2 will drop sharply by an order of magnitude and quickly transform into a low-resistance state similar to that of a metal conductor. The huge change range of resistance and the ability of rapid reversible phase transition of this material can be used in sensors to respond instantly and provide early warning for fire scenes with rapid temperature changes. However, when it is applied to temperature sensors, VO2 has a significant disadvantage. The phase transition temperature points of heating and cooling do not overlap, that is, the existence of phase transition hysteresis width. When the phase transition hysteresis width formed by this temperature difference is used in temperature sensors, the hysteresis width will cause the sensor to deviate in the measurement near the phase transition point, reduce the response speed of the sensor, and cannot accurately reflect the actual temperature change. Especially in an environment with frequent temperature fluctuations, this error will continue to accumulate, seriously affecting the accurate assessment of the ambient temperature. During long-term monitoring, the phase change process may be inconsistent due to the influence of hysteresis width in different measurements, making the measurement results unstable and repeatable, making it difficult to provide reliable continuous monitoring data.
[0004] In summary, the defects of existing temperature sensor technology and the drawbacks of vanadium oxide with hysteresis width when used in sensors greatly limit its effective application in key fields such as environmental monitoring. Therefore, there is an urgent need to develop a preparation method that can effectively eliminate or significantly reduce the hysteresis width of the vanadium oxide phase change, which is of immeasurable importance for comprehensively improving the performance of temperature sensors and vigorously promoting the development of environmental monitoring technology. Therefore, it is necessary to provide an innovative and practical solution to overcome this key technical problem and provide better quality and reliable temperature sensor technology for environmental monitoring and related fields. Therefore, the existing technology still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a narrow hysteresis width thin film material and its preparation method and application, aiming to solve the problems of low sensitivity, poor long-term stability and easy measurement deviation due to hysteresis width of existing temperature sensors.
[0006] The technical solution of this application is as follows: In a first aspect, the present application provides a narrow hysteresis width thin film material, which includes a vanadium dioxide thin film; the vanadium dioxide thin film is doped with gadolinium and titanium.
[0007] Furthermore, the doping amount of gadolinium in the narrow hysteresis width thin film material is 1at%-7.5at%, and the doping amount of titanium in the narrow hysteresis width thin film material is 1at%-10at%.
[0008] The present invention introduces magnetic rare earth elements gadolinium (Gd) and titanium (Ti) into the vanadium dioxide film as impurity ions to effectively replace or destroy the V 4+ -V 4+ Covalent bonds are formed, thereby increasing the defects in the film to regulate the phase change characteristics of the vanadium dioxide film. The provided thin film material has a narrow hysteresis width, which helps to achieve a breakthrough in the wide application of zero hysteresis width. It also has excellent reversible phase change and cycle stability as well as ultra-sensitive temperature response and fast switching characteristics, providing strong support for the development of the sensor field.
[0009] In a second aspect, the present application further provides a method for preparing a thin film material with a narrow hysteresis width as described in the first aspect, wherein the method comprises the following steps: Placing the substrate on a substrate holder in a vacuum chamber of a three-axis magnetron sputtering device, and preheating the substrate after evacuating the vacuum chamber; Argon and oxygen are introduced, the vacuum degree is adjusted to the deposition pressure, the substrate negative bias voltage and duty cycle are set, the oxygen content is adjusted, and the vanadium target is magnetron sputtered by a DC power pulse to grow vanadium dioxide on the substrate; Using the three-axis co-sputtering mode, gadolinium target and titanium target were added to co-sputter with vanadium target; After the sputtering is completed, an inert gas is introduced to perform an in-situ annealing treatment, and the heating is turned off and the mixture is cooled to room temperature to obtain the narrow hysteresis width thin film material.
[0010] Furthermore, the sputtering distance between the substrate and the target is 4-10 cm; the vacuum degree of the vacuum pump is 2×10 -4 Pa -5×10 -4 Pa; the rotation speed of the substrate rack is 10-30Hz.
[0011] Furthermore, the preheating condition is heating to 400-600°C and maintaining for 0.5-1h; The flow rate of the argon gas is 30-150 sccm, and the content of the oxygen gas is 4%-15%.
[0012] Further, the deposition pressure is 0.3-1Pa, the substrate negative bias voltage is 50-400V, the duty cycle is 10%-80%, the power supply power of the DC power pulse magnetron sputtering vanadium target is 50-400W, the pulse frequency is 40-100KHz, the interval time is 1-10us, and the sputtering time is 0.5-1h; The oxygen content is adjusted to maintain the oxygen content between 4% and 20%.
[0013] Furthermore, after the vanadium dioxide is grown for 5-20 minutes, a gadolinium target and a titanium target are added and sputtered together with the vanadium target, and the power of the radio frequency power supply for sputtering the gadolinium target and the titanium target is 5-300W.
[0014] Further, the vanadium target is pre-sputtered for 5-30 minutes before growing vanadium dioxide on the substrate; Before sputtering the gadolinium target and the titanium target, the gadolinium target and the titanium target are pre-sputtered for 5-10 minutes.
[0015] Further, the inert gas has an inlet flow rate of 10-40 sccm, and the inert gas is one or both of argon and nitrogen; The in-situ annealing treatment is carried out under the condition of keeping the temperature at 400-600° C. for 5-60 minutes.
[0016] In a third aspect, the present application further provides an application of the narrow hysteresis width thin film material as described in the first aspect, wherein the narrow hysteresis width thin film material is applied to a temperature sensor.
[0017] Beneficial effect: The present invention introduces magnetic rare earth elements gadolinium (Gd) and titanium (Ti) into the vanadium dioxide film by doping, which effectively replace or destroy the V of vanadium ions as impurity ions. 4+ -V4+ Covalent bonds are formed, thereby increasing the defects in the film to regulate the phase change characteristics of the vanadium dioxide film. The provided thin film material has a narrow hysteresis width, which helps to achieve a breakthrough in the wide application of zero hysteresis width. It also has excellent reversible phase change and cycle stability as well as ultra-sensitive temperature response and fast switching characteristics, providing strong support for the development of the sensor field. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a curve showing the change of film resistance with temperature during the heating and cooling process of the vanadium dioxide film material of Comparative Example 1 of the present application.
[0019] Figure 2 This is a Raman test image of the vanadium dioxide thin film material of Comparative Example 1 of the present application.
[0020] Figure 3 This is the curve of the change of film resistance with temperature during the heating and cooling process at different gadolinium single doping concentrations in comparative example 2 of the present application.
[0021] Figure 4 This is a curve showing the change of film resistance with temperature during the heating and cooling process of the film material of Comparative Example 3 of the present application.
[0022] Figure 5 This is a curve showing the change of film resistance with temperature during the heating and cooling process of the narrow hysteresis width film material of Example 1 of the present application.
[0023] Figure 6 This is a curve showing the change of film resistance with temperature during the heating and cooling process of the narrow hysteresis width film material of Example 2 of the present application.
[0024] Figure 7 This is a Raman test diagram of the narrow hysteresis width thin film material of Example 2 of the present application.
[0025] Figure 8 This is a curve showing the change of film resistance with temperature during the heating and cooling process of the narrow hysteresis width film material of Example 3 of the present application.
[0026] Fig. 9 This is a Raman test diagram of the narrow hysteresis width thin film material of Example 3 of the present application.
[0027] Fig.10 This is a Raman test comparison chart of the comparative example, embodiment 2 and embodiment 3 of the present application. DETAILED DESCRIPTION
[0028] The present application provides a narrow hysteresis width thin film material and a preparation method and application thereof. To make the purpose, technical solution and effect of the present application clearer and more specific, the present application is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0029] The present application provides a narrow hysteresis width thin film material, which includes a vanadium dioxide thin film; the vanadium dioxide thin film is doped with gadolinium and titanium.
[0030] The present invention introduces magnetic rare earth elements gadolinium (Gd) and titanium (Ti) into the vanadium dioxide film as impurity ions to effectively replace or destroy the V 4+ -V 4+ Covalent bonds are formed, thereby increasing the defects in the film to regulate the phase change characteristics of the vanadium dioxide film. The provided thin film material has a narrow hysteresis width, which helps to achieve a breakthrough in the wide application of zero hysteresis width. It also has excellent reversible phase change and cycle stability as well as ultra-sensitive temperature response and fast switching characteristics, providing strong support for the development of the sensor field.
[0031] In the present application, when Gd and Ti are doped into vanadium dioxide at the same time, their effects on the lattice structure and electronic structure are synergistic. The lattice expansion and overall electronic structure adjustment caused by Gd are combined with the local lattice distortion and changes in the electron scattering mechanism caused by Ti. The presence of Gd provides a more favorable lattice environment for the doping of Ti, enabling Ti to better play its regulatory role on the local structure, and the local structural changes of Ti can further promote the influence of Gd on the overall electronic structure and phase transition energy. The combined effect of the two makes the atomic motion of vanadium dioxide more coordinated during the phase transition process and the electronic behavior more orderly, thereby significantly reducing the energy hysteresis of the phase transition and further narrowing the hysteresis width.
[0032] Specifically, when gadolinium and titanium are ion-doped into vanadium dioxide (VO2) materials, the ionic radius is different from that of vanadium ions, which will cause changes in the lattice structure of vanadium dioxide. 3+ (93.8 pm) Radius greater than V 4+(63 pm), entering the lattice will cause the lattice to expand and distort. This change in the lattice structure will change the distance and direction of magnetic interaction between atoms, among which the distortion of the lattice will affect the strength and mode of magnetic coupling between Gd ions and surrounding V atoms and oxygen atoms. Lattice expansion may weaken the original magnetic exchange interaction and derive some additional magnetic interactions. Lattice distortion will change the interaction distance and bond angle between atoms, thereby affecting the distribution of the electron cloud. Gd doping narrows the band structure of vanadium dioxide and changes the state density. During the phase transition, the energy barrier that electrons need to cross also changes. The energy barrier that needs to be overcome by atomic rearrangement during the phase transition has been adjusted, and the energy change is smoother and the phase transition is more likely to occur, thereby reducing the energy hysteresis phenomenon and causing the hysteresis width to narrow. When Ti is doped into vanadium dioxide, the hysteresis width is mainly changed by affecting the crystal structure. Ti 4+ The ionic radius (about 61 pm) and V 4+ The close proximity will cause local lattice distortion, break the symmetry of the octahedron in the vanadium dioxide (R) phase, affect the forces between atoms, make atomic displacements during phase transitions easier, and reduce the energy barrier of phase transitions. During the phase transition, the atomic vibration mode and energy transfer mode change, making the energy input and release required for phase transitions more continuous, reducing the jump-like changes in energy, and thus narrowing the hysteresis width.
[0033] In addition, whether vanadium dioxide is doped with one or more rare earth elements, it ultimately destroys or replaces part of the crystal structure in a small range, that is, the effect of single ion doping (titanium or gadolinium) is limited, and the regulation of the phase change performance of vanadium dioxide from single crystal structural destruction or substitution is limited, and while changing the hysteresis width, it is often accompanied by a decrease in electrical performance. Therefore, the present application adjusts the hysteresis width through the dual effects of Ti and Gd, so that it retains some of the original characteristics while having new changes. The co-doped ions achieve a reduction in the hysteresis width while minimizing the phase change amplitude under the multiple effects of two different ion radii (one large and one small) and magnetism.
[0034] Furthermore, the doping amount of gadolinium in the thin film material with a narrow hysteresis width is 1at%-7.5at%, and the doping amount of titanium in the thin film material with a narrow hysteresis width is 1at%-10at%. In the present application, by introducing two elements, gadolinium and titanium, to replace or destroy the structure of a small part of vanadium dioxide, too high or too low doping amounts will affect the hysteresis performance and phase change performance. By controlling the doping amounts of gadolinium and titanium, a narrow hysteresis width can be obtained.
[0035] The present application can adjust key parameters such as the phase transition temperature and hysteresis width of the film by precisely controlling the type, concentration and doping method of the impurity ions, so that it has a narrow hysteresis range to achieve a fast and sensitive response.
[0036] The narrow hysteresis width thin film material provided by the present application has ultra-sensitive temperature response and fast switching characteristics. Under normal working conditions, the sensor using the thin film material of the present application can stably monitor the changes in ambient temperature. Once a sudden temperature change occurs, such as in a fire warning scenario, when the ambient temperature rises rapidly to reach or exceed the phase transition temperature of vanadium dioxide, it can instantly undergo a phase change from semiconductor to conductor, like a precise temperature trigger switch. Compared with traditional temperature sensors, its response speed advantage is significant. Traditional sensors may take several seconds or even longer to respond, while the thin film material of the present invention has a microsecond response time at the moment when the temperature triggers a phase change, which greatly improves the monitoring efficiency and early warning capability of temperature mutation events. This fast phase change characteristic enables the sensor to convert temperature changes into electrical signal changes in a very short time (milliseconds or even faster), achieve an immediate response to temperature anomalies, and issue an alarm signal in time to gain valuable time to respond to emergencies and effectively avoid significant losses caused by delayed response.
[0037] The narrow hysteresis width thin film material provided by the present application also has excellent reversible phase change and cyclic stability. During multiple temperature rise and fall cycles, the thin film material can stably switch back and forth between the semiconductor phase and the conductor phase, and the phase change performance will not show obvious attenuation. Whether it is after the temperature rises and causes the phase change, it can return to the initial semiconductor phase as the temperature decreases, or in a repeated temperature fluctuation environment, it always maintains good phase change reversibility. This feature allows the sensor to be reused many times and has extremely high reliability in long-term environmental monitoring applications. For example, temperature monitoring in industrial production processes may experience frequent temperature fluctuations, but the applied sensor can continue to work stably and provide accurate temperature data feedback for the production process, greatly reducing maintenance costs and replacement frequency, and ensuring efficient and stable operation of the production process.
[0038] The present application also provides a method for preparing the narrow hysteresis width thin film material as described above, which comprises the following steps: S1. placing the substrate on a substrate holder in a vacuum chamber of a three-axis magnetron sputtering device, and preheating the substrate after evacuating the chamber; S2, introducing argon and oxygen, adjusting the vacuum degree to the deposition pressure, setting the substrate negative bias voltage and duty cycle, adjusting the oxygen content, and growing vanadium dioxide on the substrate by pulsed magnetron sputtering of the vanadium target using a DC power supply; S3, using the three-axis co-sputtering mode, adding gadolinium target and titanium target and vanadium target for co-sputtering; S4. After the sputtering is completed, an inert gas is introduced to perform in-situ annealing treatment, and the heating is turned off and then cooled to room temperature to obtain a thin film material with a narrow hysteresis width.
[0039] Magnetron sputtering can achieve precise control of the type and content of doping elements, deposit a uniform film and achieve film performance regulation. Through the preparation process provided in this application, a layer of vanadium dioxide film is first selectively generated on the substrate as a seed layer, and then gadolinium and titanium elements are introduced. The three-axis co-sputtering mode is used to adjust the doping concentration by changing the sputtering power. During sputtering, the reaction oxygen content inside the cavity is maintained unchanged by adjusting the intake flow rate. All processes are completed at one time inside the cavity, and no multilayer structure appears. The prepared vanadium dioxide film is doped with gadolinium and titanium, thereby achieving the regulation of the narrow hysteresis width of vanadium dioxide.
[0040] Specifically, the substrate is also cleaned before deposition, including the following steps: S0. The substrate is ultrasonically cleaned in acetone, alcohol and deionized water respectively, each cleaning time is 10-30 minutes, and then blown dry with nitrogen.
[0041] Among them, by cleaning the substrate, impurities and pollutants on the substrate surface can be effectively removed, ensuring that the substrate surface is clean, providing excellent conditions for the smooth growth of the thin film, and then placed on the substrate rack in the vacuum chamber of the three-axis magnetron sputtering equipment after drying.
[0042] Furthermore, the substrate is one of silicon wafer, sapphire, mica, and quartz glass. The selected substrate material has the characteristics of flat surface and good thermal stability, laying a solid foundation for subsequent high-quality thin film growth.
[0043] Furthermore, the vanadium target is vanadium trioxide. Other targets containing vanadium sources (vanadium targets) can also be used as alternative options to meet different experimental requirements and conditions.
[0044] Furthermore, the present application uses a three-axis magnetron sputtering device, and the sputtering distance between the substrate and the three targets (vanadium target, gadolinium target, and titanium target) is set to 4-10 cm. The atoms sputtered by magnetron sputtering have higher energy, and when deposited on the substrate, the atoms can better combine with each other to form a dense film structure, reducing pores and defects in the film.
[0045] Furthermore, in step S1, the vacuum degree of the vacuum pump is 2×10 -4 Pa -5×10 -4 Pa; the rotation speed of the substrate rack is 10-30 Hz. In this application, the vacuum degree reaches 2×10 -4 Pa -5×10 - 4Pa, such a high vacuum environment can significantly reduce the adverse effects of external impurities on film growth. At the same time, the substrate rack rotates at a constant speed of 10-30Hz to ensure the uniformity of the coating, so that the film can evenly receive sputtered materials during the growth process, improving the quality and performance of the film.
[0046] Furthermore, in step S1, the preheating condition is to heat to 400-600° C. and maintain for 0.5-1 hour. This step helps to remove adsorbents and moisture on the surface of the substrate and creates suitable temperature conditions for subsequent thin film growth.
[0047] Furthermore, in step S2, the flow rate of argon gas is 30-150 sccm, and the content of oxygen gas is 4%-15%. The argon gas can be high-purity argon gas, and the content of oxygen gas can be set by an oxygen flow sensor to maintain a suitable oxygen content in the chamber.
[0048] Further, in step S2, after argon and oxygen are introduced, the vacuum is adjusted to a deposition pressure of 0.3-1Pa, the negative bias voltage of the substrate is set to 50-400V, and the duty cycle is set to 10%-80%; the power supply power of the DC power pulse magnetron sputtering vanadium target is 50-400W, the pulse frequency is 40-100KHz, the interval time is 1-10us, and the sputtering time is 0.5-1h. After adjusting the parameters, the baffle is opened to start sputtering the vanadium target, the sputtering process is oxidized, and a vanadium dioxide film is grown on the substrate. Among them, when the substrate is biased, the oxygen ions are more likely to reach the substrate surface under the action of the bias electric field and react with vanadium atoms, titanium atoms, and gadolinium atoms. The reaction process can change the combination ratio of oxygen and vanadium in the film, thereby accurately controlling the stoichiometric ratio of the vanadium oxide film and the ratio of titanium and gadolinium atoms, affecting the distribution and content of the doping elements in the film, and optimizing the composition of the film by adjusting the bias voltage to obtain a film with specific properties.
[0049] Specifically, simply ensuring that vanadium dioxide, gadolinium and titanium can be sputtered together will definitely not achieve the effect of reducing the hysteresis width. It is necessary to control the parameters so that the doped atoms replace and destroy the original structure. Simply sputtering together will have a dominant effect. In a stable environment, a small part of the vanadium atoms will be forcibly seized and impersonated by titanium or gadolinium atoms when they are combined with oxygen atoms (for example, it was originally VOV, and after the oxygen atoms were taken away, it lost part of the original structure and obtained new properties. Moreover, due to the many types and phases of vanadium oxides, only the monoclinic phase has the ability to change phases in the multi-phases of vanadium dioxide, and the common ones such as vanadium trioxide and vanadium pentoxide do not have the ability to change phases under conditions close to room temperature. The present application prepares vanadium dioxide with low-priced vanadium, creates an environment for the stable generation of vanadium dioxide for the vanadium dioxide matrix by controlling reasonable parameters, and introduces gadolinium and titanium through in-situ growth to ensure the control effect of doping on performance.
[0050] Furthermore, during the deposition process of step S2, the intake gas volume is adjusted to adjust the oxygen content to maintain the oxygen content between 4% and 20%. By creating an oxidizing atmosphere that is conducive to the growth of vanadium dioxide, the stability and consistency of the film growth are ensured. During the entire co-sputtering process, close attention is paid to the oxygen atmosphere inside the chamber to ensure that the required oxygen content is maintained, thereby ensuring that the oxidation state and phase change characteristics of the film are not affected.
[0051] Specifically, in step S3, after 5-20 minutes of growing vanadium dioxide, the baffles of the gadolinium target and the titanium target are opened respectively, and the gadolinium target and the titanium target are newly introduced for biaxial co-sputtering, and the RF power of the sputtering gadolinium target and the titanium target is 5-300 W. Among them, if the gadolinium target and the titanium target are sputtered using a DC power supply, the deposition rate will be much faster than that of vanadium dioxide, resulting in vanadium dioxide becoming the doped element, and the RF power supply is relatively slow to ensure stable deposition.
[0052] By controlling the power of the power supply, the doping amount of gadolinium and titanium can be controlled. The selected radio frequency power supply has a slow deposition rate and will not cause excessive doping. The present application first generates a layer of vanadium dioxide film on the substrate as a seed layer, and then introduces gadolinium and titanium elements during the continued growth process. Among them, the stability of the oxygen content is ensured by three-axis co-sputtering, and the gadolinium target and the titanium target provide sources. The gadolinium target and the titanium target control the doping content by power, and no other condition parameters are required to be set. A certain amount of elements is provided for the reaction by starting. During the reaction, by controlling the power, a small number of titanium atoms or gadolinium atoms bombarded by argon ion sputtering can combine with oxygen atoms in the environment to destroy or replace part of the position that originally belonged to the vanadium atoms. This oxide is not a simple oxide. The oxygen originally belonging to VO2 was originally connected to vanadium or oxygen combination. Now it can link vanadium and oxygen, and can link vanadium and titanium or gadolinium. By affecting the lattice structure, it is then deposited on the substrate with a large amount of vanadium dioxide to complete the doping and affect the hysteresis width during the phase change and achieve the improvement effect.
[0053] Furthermore, the vanadium target is pre-sputtered for 5-30 minutes before growing vanadium dioxide on the substrate; and the gadolinium target and the titanium target are pre-sputtered for 5-10 minutes before magnetron sputtering them by radio frequency power supply, respectively. By pre-sputtering before formal deposition, impurities and oxide layers on the surface of the target material can be removed.
[0054] The present application controls the doping ratio by precisely controlling the amount of oxygen in the reaction and the sputtering power of titanium and gadolinium elements, thereby ensuring that gadolinium and titanium are doped with vanadium dioxide. This can effectively adjust the phase change characteristics and hysteresis width of the vanadium dioxide film to make it more suitable for specific sensor application requirements, and avoid excessive doping resulting in oxidized vanadium doping.
[0055] Furthermore, in step S4, the inert gas flow rate is 10-40sccm, and the inert gas is one or both of argon or nitrogen, etc.; the in-situ annealing treatment condition is to keep the temperature at 400-600°C for 5-60min, preferably 30min. In the present application, by cooling to room temperature under an inert gas, the thermal stress problem caused by sudden cooling can be prevented, and the annealing treatment can further improve the crystallinity of the film, eliminate internal stress, and promote the diffusion and uniform distribution of gadolinium and titanium elements in the vanadium dioxide film, thereby improving the performance and stability of the narrow hysteresis width film.
[0056] By providing an optimized preparation method in this application, the growth of the vanadium dioxide film and the doping process of gadolinium and titanium elements can be more accurately controlled, the quality and performance of the film can be improved, and strong support can be provided for the development of the sensor field.
[0057] Specifically, the present application successfully reduces the hysteresis width of the vanadium dioxide film to near zero through an innovative preparation process, which can achieve a breakthrough in the wide application of zero hysteresis width. This breakthrough completely solves the many problems existing in the application of traditional vanadium dioxide with hysteresis width in temperature sensors. Under zero hysteresis width, the measurement accuracy of the sensor near the phase change point has been greatly improved, which can accurately reflect the actual temperature changes and avoid measurement deviations caused by hysteresis. In addition, the zero hysteresis width makes the response speed of the sensor no longer limited by the hysteresis interval, further improving the timeliness and accuracy of the response. This feature broadens the application scope of vanadium dioxide films in the field of temperature sensors and opens new doors for the application of sensor technology in more key areas.
[0058] After preparation, the obtained narrow hysteresis width film can be subjected to phase change characteristic test, electrical performance test, structural characterization, etc. to determine whether the phase change temperature and hysteresis width meet the requirements of sensor application, measure the resistance and other parameters of the film, evaluate its performance changes under different temperature conditions, and obtain a vanadium dioxide film with a specific hysteresis range that meets the needs of sensor application.
[0059] The following is further described by specific examples. Comparative Example 1 The preparation method of the vanadium dioxide thin film material of Comparative Example 1 comprises the following steps: The target material is vanadium trioxide target, the substrate is silicon wafer; the sputtering distance is set to 6cm; The silicon wafer was ultrasonically cleaned in acetone, alcohol and deionized water respectively, each time for 20 min, and then dried with nitrogen. The silicon wafer was placed on the substrate rack in the vacuum chamber of the magnetron sputtering equipment. The substrate rack rotated at a constant speed of 30 Hz and evacuated to a vacuum degree of 3×10 -4Pa, preheat the substrate to 600°C and keep it warm for 40 minutes; A high-purity argon gas with a flow rate of 80 sccm was introduced, the oxygen content was kept at 8%, the deposition pressure was 0.50 Pa, the substrate negative bias voltage was set to 200 V, the duty cycle was 50%, the power of the DC power supply pulse magnetron sputtering was 200 W, the pulse frequency was 60 KHz, the interval time was 5 us, and after pre-sputtering for 10 minutes, vanadium dioxide was grown, and the coating time was 60 minutes; Then, the oxygen gas was turned off to maintain the flow rate of argon gas at 20 sccm. After keeping the temperature for 30 minutes, the material was cooled to room temperature to obtain the vanadium dioxide thin film material of Comparative Example 1.
[0060] Comparative Example 1 was used as a control group experiment. The resistance-temperature characteristic test of the vanadium dioxide thin film material of Comparative Example 1 was carried out. The four-probe resistance measurement was adopted. The temperature was controlled at a temperature change rate of 10°C / min. The resistance change in the temperature range of 25-100°C was measured. The test results are as follows: Figure 1 As shown in FIG. 1 , the relationship between the film resistance and the temperature of the vanadium dioxide thin film material of Comparative Example 1 during the heating and cooling processes (respectively marked as Heat and Cool) is detected. It can be found that in the heating process (Heat), when the temperature reaches about 64.8°C, the film resistance begins to drop sharply, and the resistance increases from 10 4 Ω / cm rapidly decreases to 10 1 Ω / cm, which indicates that the vanadium dioxide film transforms from a semiconductor phase to a metal phase. In the cooling process (Cool), the resistance begins to rise rapidly when the temperature drops to about 54.7°C, and the film transforms from a metal phase back to a semiconductor phase.
[0061] By comparing the phase transition temperatures during the heating and cooling processes, the phase transition hysteresis width of the vanadium dioxide thin film material of Comparative Example 1 can be calculated. In this test, the hysteresis width is 10.1° C. A wider hysteresis width will affect the sensitivity and accuracy of temperature detection.
[0062] The vanadium dioxide thin film material of Comparative Example 1 was subjected to Raman testing, and the Raman pattern measured was as follows: Figure 2 As shown in the figure, it can be observed that the film sample has a peak at 193 cm -1 、224cm -1 、305cm -1 、392 cm -1 、615cm -1 There are obvious Raman peaks at all locations, which correspond to the Raman peaks of monoclinic vanadium dioxide film, among which 193.8 cm -1 and 224.6 cm -1The nearby peaks correspond to the VV vibration peaks in vanadium dioxide, and the other vibration peaks belong to VO, which show the characteristics of vanadium dioxide as a whole.
[0063] Comparative Example 2 The preparation method of four groups of thin film materials with different gadolinium contents in Comparative Example 2 comprises the following steps: Comparative Example 2: Four groups of thin film materials with different gadolinium contents were all prepared by biaxial reactive magnetron sputtering, with vanadium trioxide as the target material and sapphire as the substrate; the sputtering distance was set to 8 cm; The sapphire was ultrasonically cleaned in acetone, alcohol and deionized water respectively, each time for 15 min, and then dried with nitrogen. The silicon wafer was placed on the substrate rack in the vacuum chamber of the magnetron sputtering equipment. The substrate rack rotated at a constant speed of 30 Hz and evacuated to a vacuum degree of 2.5×10 -4 Pa, preheat the substrate to 550°C and keep warm for 30 minutes; A high-purity argon gas with a flow rate of 60 sccm was introduced, the oxygen content was kept at 7%, the deposition pressure was 0.55 Pa, the substrate negative bias voltage was set to 240 V, the duty cycle was 50%, the power of the DC power supply pulse magnetron sputtering was 250 W, the pulse frequency was 50 KHz, the interval time was 2 us, and after pre-sputtering for 10 minutes, vanadium dioxide was grown; The dual-axis co-sputtering mode was used, and gadolinium target and vanadium target were co-sputtered. The RF power of the gadolinium target in the four groups of experiments was set to 0 W, 25 W, 50 W and 80 W respectively, and the pre-sputtering was 10 minutes (the pre-sputtering of the gadolinium target and the vanadium target can be carried out together, and the shutter is opened after the pre-sputtering is completed before the formal sputtering). After the vanadium dioxide grows for 5 minutes, the gadolinium target and the vanadium target are co-sputtered for 55 minutes, and the total coating time is 60 minutes (vanadium dioxide is grown for 60 minutes in the experimental group with a gadolinium target power of 0 W, without gadolinium doping); Subsequently, oxygen was turned off to maintain an argon flow rate of 20 sccm. The mixture was kept warm for 30 minutes and then cooled to room temperature to obtain four groups of thin film materials with different gadolinium contents of Comparative Example 2. The corresponding deposited films were named VGd-0, VGd-1, VGd-2 and VGd-3.
[0064] The gadolinium contents of the films of VGd-0, VGd-1, VGd-2 and VGd-3 of Comparative Example 2 were calculated by XPS, and the results are shown in Table 1: Table 1 Group Gadolinium target RF power supply power (W) Gadolinium doping content (at%) VGd-0 0 0 VGd-1 25 1.8 VGd-2 50 3.7 VGd-3 80 7.5 Comparative Example 2 The thin film materials with different Gd contents were subjected to the same resistance-temperature characteristic test as in Comparative Example 1. The test results are shown in FIG. Figure 3As shown in Figure 2, the phase transition temperatures (T) of VGd-0, VGd-1, VGd-2 and VGd-3 during the heating process (Heat) and cooling process (Cool) H 、T C ) and hysteresis width (△H) data are shown in Table 2: Table 2 Group <![CDATA[T H (℃)]]> <![CDATA[T C (℃)]]> △H(℃) VGd-0 66.2 56.9 9.3 VGd-1 60.8 52.2 8.6 VGd-2 55.4 47.9 7.5 VGd-3 -- -- -- It can be found that single doping will destroy the VV bond around the C axis of the vanadium dioxide crystal to a certain extent, change the structural integrity to a certain extent, and thus reduce the hysteresis width or change the phase transition temperature. Using only one of the elements will greatly reduce the resistance value ratio before and after the phase transition. Figure 3 (VGd-0 is undoped resistance, and the phase transition ability disappears when it increases to VGd-3) The resistance change of single Gd doping can be observed. With the addition of Gd, the phase transition temperature decreases and the hysteresis width decreases. Although the hysteresis width can be reduced, it can no longer meet the application requirements. Vanadium dioxide itself has a certain magnetic property, and its magnetic property will change during the phase transition. Under certain conditions, the magnetic moment of vanadium dioxide interacts with the electrons and lattice in the material, which may affect the energy balance during the phase transition and the phase stability after the phase transition. Therefore, it is necessary to dope the gadolinium element (Gd 3+ ) and other elements (Ti 4+ ) jointly regulate the magnetic and phase change properties of vanadium dioxide.
[0065] Comparative Example 3 Comparative Example 3 The method for preparing the overdoped thin film material comprises the following steps: The target material is vanadium trioxide target, and the substrate is sapphire; the sputtering distance is set to 10 cm (Comparative Example 3 uses a larger power, increases the sputtering distance, and the end distribution is more uniform); The sapphire was ultrasonically cleaned in acetone, alcohol and deionized water respectively, each time for 20 min, and then dried with nitrogen. The silicon wafer was placed on the substrate rack in the vacuum chamber of the three-axis magnetron sputtering equipment. The substrate rack rotated at a constant speed of 30 Hz and evacuated to a vacuum degree of 4×10 -4 Pa, preheat the substrate to 550°C and keep warm for 30 minutes; A high-purity argon gas with a flow rate of 50 sccm was introduced, the oxygen content was kept at 8.5%, the deposition pressure was 0.60 Pa, the substrate negative bias voltage was set to 240 V, the duty cycle was 50%, the power of the DC power supply pulse magnetron sputtering was 250 W, the pulse frequency was 50 KHz, the interval time was 2 us, and after pre-sputtering for 10 minutes, vanadium dioxide was grown; Use the three-axis co-sputtering mode, add gadolinium target and titanium target and vanadium target for co-sputtering, the sputtering power of gadolinium target and titanium target RF power supply is 150W and 200W respectively, pre-sputtering for 5 minutes, after vanadium dioxide coating for 5 minutes, vanadium dioxide and gadolinium titanium three-axis co-sputtering for 300 minutes, the total coating time is 35 minutes (the power increases, the deposition rate also increases accordingly, and the time should be reduced accordingly, because the generation rate of vanadium dioxide is much slower than that of titanium and gadolinium, and the proportion of vanadium dioxide will continue to decrease over time); Then, the oxygen was turned off to maintain the inflow rate of argon at 15 sccm. After keeping the temperature for 30 minutes, the mixture was cooled to room temperature to obtain the thin film material of Comparative Example 3.
[0066] XPS measured that the doping amount of gadolinium in the thin film material prepared in Comparative Example 3 was 9.8 at%, and the doping amount of titanium was 11.5 at%. The same test method as that of Comparative Example 1 was used to test the resistance-temperature characteristics of the thin film material prepared in Comparative Example 3. The results are as follows: Figure 4 As shown, it can be found that the doping element in the thin film material of Comparative Example 3 becomes the main component under excessive doping, which affects the characterization of the phase change performance of vanadium dioxide.
[0067] Example 1 The method for preparing the narrow hysteresis width thin film material of Example 1 comprises the following steps: The target material is vanadium trioxide target, the substrate is sapphire; the sputtering distance is set to 8cm; The sapphire was ultrasonically cleaned in acetone, alcohol and deionized water respectively, each time for 20 min, and then dried with nitrogen. The silicon wafer was placed on the substrate rack in the vacuum chamber of the three-axis magnetron sputtering equipment. The substrate rack rotated at a constant speed of 30 Hz and evacuated to a vacuum degree of 4×10 -4 Pa, preheat the substrate to 550°C and keep warm for 30 minutes; A high-purity argon gas with a flow rate of 50 sccm was introduced, the oxygen content was kept at 8%, the deposition pressure was 0.55 Pa, the substrate negative bias voltage was set to 240 V, the duty cycle was 50%, the power of the DC power supply pulse magnetron sputtering was 250 W, the pulse frequency was 50 KHz, the interval time was 2 us, and after pre-sputtering for 10 minutes, vanadium dioxide was grown; The three-axis co-sputtering mode was used. The gadolinium target and titanium target were added to co-sputter with the vanadium target. The sputtering powers of the gadolinium target and titanium target RF power supply were 20W and 20W respectively. The pre-sputtering was 5 minutes. After vanadium dioxide was coated for 5 minutes, vanadium dioxide and gadolinium titanium were co-sputtered for 60 minutes in three axes. The total coating time was 65 minutes. Then, the oxygen gas was turned off to maintain the flow rate of argon gas at 15 sccm. After keeping the temperature for 30 minutes, the thin film material with narrow hysteresis width of Example 1 was obtained.
[0068] The XPS measurement shows that the gadolinium doping amount of the narrow hysteresis width thin film material prepared in Example 1 is 1.7 at%, and the titanium doping amount is 1.42 at%. The resistance-temperature characteristic test of the narrow hysteresis width thin film material prepared in Example 1 is carried out using the same test method as that of Comparative Example 1. The results are as follows: Figure 5 As shown in FIG. 1 , the relationship between the film resistance and the temperature of the narrow hysteresis width film material of Example 1 during the heating and cooling processes (respectively marked as Heat and Cool) is detected. In the heating process (Heat), when the temperature reaches about 59.5°C, the film resistance begins to drop sharply, and the resistance increases from 10 5 Ω / cm rapidly decreases to 10 2 Ω / cm, which indicates that the vanadium dioxide film transforms from a semiconductor phase to a metal phase. In the cooling process (Cool), the resistance begins to rise rapidly when the temperature drops to about 56.3°C, and the film transforms from a metal phase back to a semiconductor phase.
[0069] By comparing the phase transition temperatures during the heating and cooling processes, the phase transition hysteresis width of the narrow hysteresis width film material of Example 1 can be calculated. In this test, the hysteresis width is 3.2° C. Compared with Comparative Example 1, the hysteresis width of Example 1 is significantly reduced.
[0070] Example 2 The method for preparing the narrow hysteresis width thin film material of Example 2 comprises the following steps: The target material is vanadium trioxide target, the substrate is silicon wafer; the sputtering distance is set to 8cm; The silicon wafer was ultrasonically cleaned in acetone, alcohol and deionized water respectively, each time for 20 min, and then dried with nitrogen. The silicon wafer was placed on the substrate rack in the vacuum chamber of the three-axis magnetron sputtering equipment. The substrate rack rotated at a constant speed of 30 Hz and evacuated to a vacuum degree of 3.5×10 -4 Pa, preheat the substrate to 600°C and keep it warm for 45 minutes; A high-purity argon gas with a flow rate of 50 sccm was introduced, the oxygen content was kept at 8%, the deposition pressure was 0.55 Pa, the substrate negative bias voltage was set to 240 V, the duty cycle was 50%, the power of the DC power supply pulse magnetron sputtering was 250 W, the pulse frequency was 60 KHz, the interval time was 4 us, and after pre-sputtering for 10 minutes, vanadium dioxide was grown; The three-axis co-sputtering mode was used, and gadolinium target and titanium target were added to co-sputter with vanadium target. The sputtering power of the gadolinium target and titanium target RF power supply was 50W and 75W respectively. The pre-sputtering was 5 minutes. After vanadium dioxide coating for 10 minutes, vanadium dioxide and gadolinium titanium were co-sputtered for 50 minutes in three axes, and the total coating time was 60 minutes. Then, the oxygen gas was turned off to maintain the flow rate of argon gas at 20 sccm. After keeping the temperature for 40 minutes, the thin film material with narrow hysteresis width of Example 2 was obtained.
[0071] The XPS measurement shows that the gadolinium doping amount of the narrow hysteresis width thin film material prepared in Example 2 is 3.71 at%, and the titanium doping amount is 4.86 at%. The resistance-temperature characteristic test of the narrow hysteresis width thin film material prepared in Example 2 is carried out using the same test method as in Comparative Example 1. The results are as follows: Figure 6 As shown in FIG. 1 , the relationship between the film resistance and the temperature of the narrow hysteresis width film material of Example 2 during the heating and cooling processes (respectively marked as Heat and Cool) is detected. In the heating process (Heat), when the temperature reaches about 65.6°C, the film resistance begins to drop sharply, and the resistance increases from 10 5 Ω / cm rapidly decreases to 10 2 Ω / cm, which indicates that the vanadium dioxide film transforms from a semiconductor phase to a metal phase. In the cooling process (Cool), the resistance begins to rise rapidly when the temperature drops to about 64.7°C, and the film transforms from a metal phase back to a semiconductor phase.
[0072] By comparing the phase transition temperatures during the heating and cooling processes, the phase transition hysteresis width of the narrow hysteresis width thin film material of Example 2 can be calculated. In this test, the hysteresis width is 0.9°C. Compared with Comparative Example 1, the hysteresis width of Example 2 is significantly reduced. The hysteresis width of 0.9°C can reduce the response speed of the sensor limited by the hysteresis interval, further improving the timeliness and accuracy of the response.
[0073] The narrow hysteresis width thin film material of Example 2 was subjected to Raman testing, and the measured Raman pattern was as follows: Figure 7 As shown, it can be observed that the film sample has a peak at 187.3 cm -1 、219.5cm -1 、302.7cm -1 、390.4 cm -1 、613.8cm -1 There are obvious Raman peaks at all places. Compared with comparative example 1, these peaks have shifted to the left. This is because the titanium or gadolinium atoms replace the positions originally belonging to vanadium, which will cause the original VV bonds and VO bonds to change, which is manifested as the shift of the Raman peak position. The result is that it shifts to the left. It can be seen that the doping of gadolinium and titanium effectively destroys the V 4+ -V 4+ Covalent bonds are used to increase defects in the film to regulate the phase change characteristics of the vanadium dioxide film.
[0074] Example 3 The method for preparing the narrow hysteresis width thin film material of Example 3 comprises the following steps: The target material is vanadium trioxide target, the substrate is silicon wafer; the sputtering distance is set to 10cm; The silicon wafer was ultrasonically cleaned in acetone, alcohol and deionized water respectively, each time for 20 min, and then dried with nitrogen. The silicon wafer was placed on the substrate rack in the vacuum chamber of the three-axis magnetron sputtering equipment. The substrate rack rotated at a constant speed of 30 Hz and evacuated to a vacuum degree of 4×10 -4 Pa, preheat the substrate to 550°C and keep warm for 30 minutes; A high-purity argon gas with a flow rate of 50 sccm was introduced, the oxygen content was kept at 8%, the deposition pressure was 0.55 Pa, the substrate negative bias voltage was set to 240 V, the duty cycle was 50%, the power of the DC power supply pulse magnetron sputtering was 250 W, the pulse frequency was 50 KHz, the interval time was 2 us, and after pre-sputtering for 10 minutes, vanadium dioxide was grown; The three-axis co-sputtering mode was used. The gadolinium target and titanium target were co-sputtered with the vanadium target. The sputtering powers of the gadolinium target and titanium target RF power supply were 40W and 80W respectively. The pre-sputtering lasted for 5 minutes. After vanadium dioxide was coated for 5 minutes, vanadium dioxide and gadolinium titanium were co-sputtered for 60 minutes in three axes. The total coating time was 65 minutes. Then, the oxygen gas was turned off to maintain the flow rate of argon gas at 15 sccm. After keeping the temperature for 30 minutes, the material was cooled to room temperature to obtain the narrow hysteresis width thin film material of Example 3.
[0075] The XPS measurement shows that the gadolinium doping amount of the narrow hysteresis width thin film material prepared in Example 3 is 3.12 at%, and the titanium doping amount is 5.14 at%. The resistance-temperature characteristic test of the narrow hysteresis width thin film material prepared in Example 3 is carried out by the same test method as in Comparative Example 1. The results are as follows: Figure 8 As shown, the relationship between the film resistance and temperature of the narrow hysteresis width film material of Example 3 during the heating and cooling processes (respectively marked as Heat and Cool) is detected. In the heating process (Heat), when the temperature reaches about 65.1°C, the film resistance begins to drop sharply, and the resistance increases from 10 4 Ω / cm rapidly decreases to 10 2 Ω / cm, which indicates that the vanadium dioxide film transforms from a semiconductor phase to a metal phase. In the cooling process (Cool), the resistance begins to rise rapidly when the temperature drops to about 65.0°C, and the film transforms from a metal phase back to a semiconductor phase.
[0076] By comparing the phase transition temperatures during the heating and cooling processes, the phase transition hysteresis width of the narrow hysteresis width thin film material of Example 3 can be calculated. In this test, the hysteresis width is 0.1°C. Compared with Comparative Example 1, the hysteresis width of Example 3 is significantly reduced. The 0.1°C hysteresis width can further reduce the response speed of the sensor limited by the hysteresis interval, greatly improving the timeliness and accuracy of the response.
[0077] The narrow hysteresis width thin film material of Example 3 was subjected to Raman testing, and the measured Raman pattern is as follows: Fig. 9 As shown, it can be observed that the film sample has a peak at 184.6 cm -1 、217.9cm -1 、300.8cm -1 、387.9 cm -1 、609.6cm -1 There are obvious Raman peaks at all places. Compared with comparative example 1, these peaks have shifted to the left to a certain extent. It can be seen that the doping of gadolinium and titanium effectively destroys the V 4+ -V 4+ Covalent bonds increase the defects in the film to regulate the phase change characteristics of the vanadium dioxide film, reducing the hysteresis width while minimizing the loss of electrical properties.
[0078] The Raman spectra of Comparative Example 1, Example 2 and Example 3 are compared as shown in FIG. Fig.10 As shown, it provides intuitive data support for process optimization. It can be found that these peaks have shifted to the left compared with comparative example 1. The doping of gadolinium and titanium effectively destroys V 4+ -V 4+ Covalent bonds increase the defects in the film, resulting in a significant change in the phase transition hysteresis width of the vanadium dioxide film.
[0079] When gadolinium and titanium are ion-doped into vanadium dioxide (VO2) materials, they cause lattice distortion due to the difference in ion radius from vanadium ions. 3+ (93.8 pm) Radius greater than V 4+ (63 pm) will expand the lattice and have a certain degree of magnetism. After doping, its magnetic moment interacts with the electrons and lattice in the material, which may change the energy balance during the phase transition. The magnetic interaction may promote or hinder the occurrence of phase transition, or affect the phase stability after the phase transition. 4+ (61 pm) radius is smaller than V 4+, which will cause the lattice to shrink. The lattice distortion under the action of gadolinium and titanium dual ions changes the periodic potential field of the crystal, affecting the band structure and transition behavior of the electrons. In the Raman spectrum, the lattice vibration mode changes, resulting in the displacement and peak shape of the Raman peak. The Raman peak moves toward the low frequency direction, indicating that the lattice vibration frequency is reduced. This is because the lattice distortion changes the bond length and bond angle between atoms. The weakening of the interaction force between atoms will change the amplitude and speed of this resistance change, which in turn affects the electrical signal response characteristics to temperature changes in applications such as sensors.
[0080] The introduction method of gadolinium and titanium elements in this application is the key innovation of this application in regulating the phase change characteristics of vanadium dioxide film. Through the three-axis co-sputtering mode, gadolinium and titanium elements are introduced at a specific process stage to increase the effective defects of the film, and the regulation of the doping concentration is achieved by changing the power of the RF magnetron sputtering power supply of the target material in the range of 0-300W. Accurate control of the doping concentration can directly affect the number and distribution of defects formed in the film, thereby adjusting the phase change temperature and hysteresis width of the film. Different application scenarios may have different requirements for phase change temperature and hysteresis width, and the process of the present invention can be flexibly adjusted according to actual needs. During the entire co-sputtering process, it is very important to maintain the oxygen atmosphere inside the cavity unchanged. The stability of the oxygen content can ensure the stability of the oxidation state of the film, avoid fluctuations in the composition and structure of the film due to changes in the oxidizing environment, and thus ensure that the phase change characteristics of the film are predictable and stable. Any behavior that does not adopt the Gd and Ti doping process of this application or fails to maintain the same process conditions to try to achieve similar vanadium dioxide film performance, infringes the intellectual property rights of the present invention.
[0081] It should be understood that the application of the present application is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made according to the above description, and all these improvements and changes should fall within the scope of protection of the present application.
Claims
1. A narrow hysteresis width thin film material, characterized in that: The invention comprises a vanadium dioxide film; the vanadium dioxide film is doped with gadolinium and titanium.
2. The narrow hysteresis width thin film material according to claim 1, characterized in that: The doping amount of gadolinium in the narrow hysteresis width thin film material is 1 at %-7.5 at %, and the doping amount of titanium in the narrow hysteresis width thin film material is 1 at %-10 at %.
3. A method for preparing a thin film material with a narrow hysteresis width as claimed in any one of claims 1 or 2, characterized in that: The following steps are involved: Placing the substrate on a substrate holder in a vacuum chamber of a three-axis magnetron sputtering device, and preheating the substrate after evacuating the vacuum chamber; Argon and oxygen are introduced, the vacuum degree is adjusted to the deposition pressure, the substrate negative bias voltage and the duty cycle are set, the oxygen content is adjusted, and a vanadium target is magnetron sputtered by a direct current power pulse to grow vanadium dioxide on the substrate; Using the three-axis co-sputtering mode, gadolinium target and titanium target were added to co-sputter with vanadium target; After the sputtering is completed, an inert gas is introduced to perform an in-situ annealing treatment, and the heating is turned off and the mixture is cooled to room temperature to obtain the narrow hysteresis width thin film material.
4. The method for preparing a thin film material with a narrow hysteresis width according to claim 3, characterized in that: The sputtering distance between the substrate and the target is 4-10 cm; the vacuum degree of the vacuum pump is 2×10 -4 Pa -5×10 -4 Pa; the rotation speed of the substrate rack is 10-30Hz.
5. The method for preparing a thin film material with a narrow hysteresis width according to claim 3, characterized in that: The preheating condition is to heat to 400-600°C and maintain for 0.5-1h; The flow rate of the argon gas is 30-150 sccm, and the content of the oxygen gas is 4%-15%.
6. The method for preparing a thin film material with a narrow hysteresis width according to claim 3, characterized in that: The deposition pressure is 0.3-1Pa, the substrate negative bias voltage is 50-400V, the duty cycle is 10%-80%, the power supply power of the DC power pulse magnetron sputtering vanadium target is 50-400W, the pulse frequency is 40-100KHz, the interval time is 1-10us, and the sputtering time is 0.5-1h; The oxygen content is adjusted to maintain the oxygen content between 4% and 20%.
7. The method for preparing a thin film material with a narrow hysteresis width according to claim 3, characterized in that: After growing vanadium dioxide for 5-20 minutes, a gadolinium target and a titanium target are added and sputtered together with the vanadium target. The power of the radio frequency power supply for sputtering the gadolinium target and the titanium target is 5-300W.
8. The method for preparing a thin film material with a narrow hysteresis width according to claim 3, characterized in that: Pre-sputtering the vanadium target for 5-30 minutes before growing vanadium dioxide on the substrate; Before sputtering the gadolinium target and the titanium target, the gadolinium target and the titanium target are pre-sputtered for 5-10 minutes.
9. The method for preparing a thin film material with a narrow hysteresis width according to claim 3, characterized in that: The inert gas has an inlet flow rate of 10-40 sccm, and the inert gas is one or both of argon and nitrogen; The in-situ annealing treatment is carried out under the condition of keeping the temperature at 400-600° C. for 5-60 minutes.
10. An application of the narrow hysteresis width thin film material as claimed in claim 1, characterized in that: The narrow hysteresis width thin film material is applied to a temperature sensor.
Citation Information
Patent Citations
Method for controlling phase transition of hydrogen-containing transition metal oxides
CN108091760A
Production of thermochromic vanadium dioxide particulate material
WO2024205406A1
Cited By
YIG material for substrate surface sputtering and preparation method thereof
CN120249880A